Liver tumor potency indicators for technical toxaphene and congeners simulating weathered toxaphene. Issue 3 (3rd April 2018) - Kerger, Brent D.; Bogen, Kenneth T.; Loccisano, Anne E.; Lamb, James C.
ABSTRACT: Technical toxaphene (TT) is a liver tumor promoter in B6C3F1 mice but not in F344 rats. To further evaluate dose-response relationships for weathered toxaphene, B6C3F1 mouse hepatocytes were treated with TT alone, five selected persistent congeners (p-26, p-50, p-62, Hx-Sed, and Hp-Sed), or two selected congener mixtures (simulating weathered toxaphene) and dose-response relationships were characterized for cytotoxicity and gap junction intercellular communication (GJIC) inhibition. Phenobarbital was included as a positive control for mouse liver tumor promotion and GJIC inhibition and dose ranges were calibrated to define benchmark dose concentrations. Each treatment group exhibited significant cytotoxicity and GJIC inhibition for at least one sex (M/F) after 3 and/or 24 h of treatment. Maximum GJIC inhibition was observed at certain noncytotoxic concentrations with sex-specific differences in relative potency estimated as the effective concentration at 20% inhibition (EC20); however, no significant EC20 differences were observed between the treatment groups. Analysis of mixture interactions at the EC20 showed that GJIC inhibition of the two weathered toxaphene mixtures was significantly less than additive compared to that for the component congeners. These findings suggest that the persistent toxaphene congener mixtures tested are not more tumorigenic than the parent insecticide mixture.